Contribution to the study of Epeorus Eaton, 1881 (Ephemeroptera: Heptageniidae) from India - Vasanth, M.; Selvakumar, C.; Subramanian, K. A.; Sivaramakrishnan, K. G.; Sinha, Bikramjit (Zootaxa, 2021)
Seven species of the genus Epeorus Eaton, 1881 are described so far from India of which redescription is attempted herein for 3 species viz. E. (C.) psi Eaton 1883, E. (E.) gilliesi Braasch 1981, E. (E.) petersi Sivaruban, Venkataraman & Sivaramakrishnan 2013 based on the fresh collections. Four species viz., E. (E.) aculeatus Braasch 1990, E. (E.) bifurcatus Braasch & Soldán 1979, E. (E.) unicornutus Braasch 2006 and E. (E.) unispinosus Braasch 1980 are new records to this country. Totally, 11 species of the genus Epeorus from India are dealt with herein of which six belongs to the subgenus Epeorus viz. E. (E.) aculeatus Braasch 1990, E. (E.) bifurcatus Braasch & Soldán 1979, E. (E.) gilliesi Braasch, 1981 and E. (E.) petersi Sivaruban, Venkataraman & Sivaramakrishnan 2013, E. (E.) unispinosus Braasch 1980, E. (E.) unicornutus Braasch 2006 and four to the subgenus Caucasiron viz., E. (C.) kapurkripalanorum Braasch 1983, E. (C.) papillatus Braasch, 2006a, E. (C.) psi Eaton 1883 which larva is described in details for the first time and E. (C.) suspicatus Braasch, 2006b . The subgeneric status of E. lahaulensis Kapur & Kripalani 1963 cannot be fixed due to non-availability of larval description. A dichotomous key to the larvae of available species in India is presented. Distribution of subgenera and species within India is discussed.